Atom search optimization based study of frequency deviation response of a hybrid power system - Khokhar, Bhuvnesh; Dahiya, Surender; Singh Parmar, K. P. (Proceedings of ... IEEE Power India International Conference (Online), 2020)
This paper attempts a maiden application of a newly developed Atom Search Optimization (ASO) algorithm for the load frequency control (LFC) of a hybrid power system (HPS). The investigated HPS consists of conventional as well as distributed generation (DG) sources. An ASO algorithm based integer order proportional integral derivative (PID) controller is implemented as the LFC controller. A comparative analysis of frequency deviation response (FDR) of the HPS subject to multiple disturbances in load and wind power is presented. The simulation results demonstrate a superior performance of the proposed algorithm compared to the other algorithms. Additionally, operational stability of the HPS is established via Bode diagram and Eigen values.